2014
DOI: 10.1371/journal.pone.0113450
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Syndrome with Decreased Glomerular Filtration Rate among 75,468 Chinese Adults: A Cross-Sectional Study

Abstract: BackgroundThe impact of the various elements of metabolic syndrome (MetS) on chronic kidney disease (CKD) has been conflicting. Therefore, in the present study we aimed to examine the association of MetS and its components with decreased glomerular filtration rate (GFR).MethodsA total of 75,468 urban workers who underwent annual health examinations under the auspices of the local governments between March 2010 and September 2012 at the health examination center of Xuzhou center hospital were enrolled in the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
5
29
4
1
Order By: Relevance
“…This result was similar to those in previous reports by Song et al [31] and Kang et al [5] However, no positive association between elevated plasma glucose, elevated WC, and CKD was shown in a cross-sectional study of 6,217 U.S. adults [32]. In another study, elevated TG and obesity were regarded as noncritical components of metabolic syndrome [31]. The multivariate-adjusted ORs of decreased GFR were not significant for those with 1 or 2 noncritical components (versus zero components).…”
Section: Metabolic Syndrome and Chronic Kidney Diseasesupporting
confidence: 94%
See 2 more Smart Citations
“…This result was similar to those in previous reports by Song et al [31] and Kang et al [5] However, no positive association between elevated plasma glucose, elevated WC, and CKD was shown in a cross-sectional study of 6,217 U.S. adults [32]. In another study, elevated TG and obesity were regarded as noncritical components of metabolic syndrome [31]. The multivariate-adjusted ORs of decreased GFR were not significant for those with 1 or 2 noncritical components (versus zero components).…”
Section: Metabolic Syndrome and Chronic Kidney Diseasesupporting
confidence: 94%
“…Kang et al [5]also demonstrated a 1.53-fold increased ORs for CKD in Koreans with metabolic syndrome based on the general health screening data of 10,253,085 participants. Consistent with these findings, the positive effects of metabolic syndrome on the prevalence of CKD were shown in several studies [6][7][8]31]. In the present study, we showed that metabolic syndrome was significantly associated with a 1.49-fold increased OR for CKD.…”
Section: Metabolic Syndrome and Chronic Kidney Diseasesupporting
confidence: 93%
See 1 more Smart Citation
“…14,25 More recently, obesity, as an emerging threat, has also played a major role in the progression of CKD. 5,26 Though in multivariable analysis, association of BMI with CKD turned positively on a certain level, as the case in DBP, the deep going research showed male and female have thus opposite effects on the links between BMI and decreased eGFR, which can especially be seen from the chart ( Figure 1F). Though we have found obesity is a noncritical factor previously, 5 the U-shaped association between BMI and decreased eGFR is also presented in multivariable analysis.…”
Section: Discussionmentioning
confidence: 87%
“…4 Therefore, it is vital to better understand the pathogenesis of CKD so as to formulate prophylactic strategies. 5 Metabolic syndrome (MetS), characterized by hypertriglyceridemia, abdominal obesity, depressed serum high-density lipoprotein cholesterol (HDL-C), diabetes mellitus, and hypertension, is commonly found in CKD sufferers. 6,7 Substantial evidence confirmed that MetS and its contributors play a critical role in the progression of CKD.…”
Section: Introductionmentioning
confidence: 99%